EFEKTIFITAS E–FILING TERHADAP PENINGKATAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI DENGAN TINGKAT KEAMANAN DAN KERAHASIAAN SEBAGAI VARIABEL MODERASI: Studi Empiris Pada Kantor Pelayanan Pajak Pratama Badung Utara - I Ketut Yudana Adi (Badung: LPPM Universitas Triatma Mulya, 2020)
This study discusses the influence the effectiveness of e-filing to Increase TaxpayerCompliance with Level of Security and Privacy as a variable Moderation on KPP Pratama Badung Utara. The data in this study was obtained from questionnaires distributed to taxpayers using random sampling method. Respondents were used in this study as many as 98 respondents. Hypothesis test used is simple linear regression and Moderated Regression Analysis. The results of this study indicate hat (1) the effectiveness of e-filing and significant positive effect on the Improvement of Taxpayer Compliance. This is proved by simple linear regression analysis obtained showed the value of R Square of 0.135. (2) Security and confidentiality can moderate (strengthen) influence the effectiveness of e-filing to increase compliance individual taxpayers registered in KPP Pratama Badung Utara. This is evidenced through the analysis performed using Moderated Regression Analysis technique that provides value R square of 0.416.